Loss of Wood Formation Genes in Monocot Genomes - Roodt, Danielle (Genome Biol Evol, 2019)
Woodiness (secondary xylem derived from vascular cambium) has been gained and lost multiple times in the angiosperms, but has been lost ancestrally in all monocots. Here, we investigate the conservation of genes involved in xylogenesis in fully sequenced angiosperm genomes, hypothesizing that monocots have lost some essential orthologs involved in this process. We analyzed the conservation of genes preferentially expressed in the developing secondary xylem of two eudicot trees in the sequenced genomes of 26 eudicot and seven monocot species, and the early diverging angiosperm Amborella trichopoda. We also reconstructed a regulatory model of early vascular cambial cell identity and differentiation and investigated the conservation of orthologs across the angiosperms. Additionally, we analyzed the genome of the aquatic seagrass Zostera marina for additional losses of genes otherwise essential to, especially, secondary cell wall formation. Despite almost complete conservation of orthology within the early cambial differentiation gene network, we show a clear pattern of loss of genes preferentially expressed in secondary xylem in the monocots that are highly conserved across eudicot species. Our study provides candidate genes that may have led to the loss of vascular cambium in the monocots, and, by comparing terrestrial angiosperms to an aquatic monocot, highlights genes essential to vasculature on land.